IMPLEMENTASI MODEL PEMBELAJARAN TSTS DALAM PENDIDIKAN PANCASILA: STUDI KASUS DI KELAS VI SDN 1 TANJUNG MAKMUR - Reni Marlina; Hetilaniar; Kusuma Putri, Mega (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how the Two Stay Two Stray (TSTS) cooperative learning model is implemented in Pancasila Education classes at grade VI of SDN 1 Tanjung Makmur. Data were collected through participatory observation, in-depth interviews with teachers, students, the principal, and parents, and document analysis. The entire process followed a qualitative case study design. TSTS implementation unfolded through four stages, namely heterogeneous group formation, group discussion, stay-stray rotation, and synthesis. Each stage produced distinct interaction patterns, psychological dynamics, and teaching challenges. Three contextual factors shaped implementation quality, namely teacher facilitation skills, group dynamics, and students' prior communicative ability. The stay-stray rotation proved to be the most demanding stage, and also the most pedagogically rich, requiring students to draw on cognitive, communicative, and emotional readiness at once. Of all the findings, one stands out there is a natural fit between how TSTS works and what Pancasila values ask of students. Learning through TSTS is, in practice, a direct exercise in mutual cooperation, deliberation, and respect for difference. The study contributes a process-oriented understanding of TSTS that moves beyond outcome measurement, and points to practical directions for developing teachers' facilitation skills in civic and character education.